Análise da política pública da Educação de Jovens e Adultos (EJA) na Escola Municipal de Ensino Fundamental Estudante Ana Beatriz Macedo Tavares Marques em Maracanaú-CE: impactos na vida dos alunos - Mendonça, Josylene Fagundes (2024)
The public policy on Youth and Adult Education aims to provide opportunities for people who did not have access to regular education at the correct age to complete their studies in a shorter time and with methodologies adapted to the needs of adult students. Due to its ability to change people's lives, there was an interest in researching more about the impacts that this policy has on the lives of the people it serves. The central problem to be addressed in this study is: How the EJA public policy in Maracanaú-CE is being implemented and what are the impacts of this implementation on the lives of students, considering access to education, academic performance and employability at the stage school of research? Furthermore, how can the perspective of these actors positively influence the effectiveness of this public policy? This dissertation has as its methodology the evaluative perspective according to Lejano (2012) who defends a complete analysis where considering the different perspectives that emerge from the dimension of experience and understanding, to attribute components in the exercise of analysis and evaluation of public policies, specifically the evaluation in depth advocated by Rodrigues (2008) and Rodrigues (2016) who uses field research as a way of delving broadly and deeply into the socio, historical and cultural context of a policy, in this research the EJA policy. To do this, we used the analysis technique, aiming to uncover the four main actors present within the context of EJA. The general objective of this dissertation is to analyze the public policy of EJA at the Ana Beatriz Macedo Tavares Marques Municipal Student School located in the municipality of Maracanaú. The specific objectives are: (1) to assess the impacts of EJA on students’ lives; (2) analyze how participation in EJA affects students' employability, professional opportunities and quality of life; (3) investigate the perspective of students, teachers, families and the school management nucleus on the implementation of the EJA public policy in the analyzed school unit. It was possible to analyze EJA's public policy at EMEF Student Ana Beatriz Macedo Tavares Marques and an important aspect was concluded; there is a congruent vision between the four audiences studied. Everyone understands that EJA brings favorable results in the lives of students. EJA is a highly valuable tool for the development of society, as it aims to alleviate the absence of the State in the role of executing everyone's right to fair and equal education.